Planning Approach of Kebayoran New City of Jakarta: Background and Lessons Learned - Fahmi, Erwin (Journal of Regional and City Planning, 2021)
The planning of Kebayoran Baru in 1948 marked the end, and perhaps the peak, of the achievements of town planning in the Dutch East Indies. In this era, a different planning approach was applied than the one used today. This study examines that approach, the challenges it faced, and the lessons learned for current and future eras. Kebayoran Baru was meant to provide housing and office buildings in view of the expected economic growth of the colony, which had begun at the turn of the century. However, its construction was only done after World War II in the context of city reconstruction. The planning of Kebayoran Baru utilized the accumulation of knowledge concerning the principles, methods, and practice of town planning in the archipelago formulated in the third decade of the century. Instrumental to the planning of Kebayoran Baru were two prominent figures: H. Mohammad Soesilo and Thomas Karsten. Two of Karsten’s conceptual legacies that Soesilo applied in the planning of Kebayoran Baru, i.e. the concepts of ‘social mix’ and ‘organic whole’, were also relevant for post-independence Indonesia (to be). Abstrak. Perencanaan Kebayoran Baru pada tahun 1948 menandai akhir, dan mungkin puncak, dari pencapaian tata kota di Hindia Belanda. Di era ini, pendekatan perencanaan yang diterapkan berbeda dari yang digunakan dahulu. Studi ini mengkaji pendekatan tersebut, tantangan yang dihadapinya, dan pembelajaran untuk era saat ini dan masa depan. Sejak pergantian abad, Kebayoran Baru dimaksudkan untuk menyediakan perumahan dan gedung perkantoran demi mengakomodasi pertumbuhan ekonomi koloni. Walaupun demikian, pembangunan tersebut dilakukan setelah Perang Dunia II dalam rangka rekonstruksi kota. Perencanaan Kebayoran Baru memanfaatkan akumulasi pengetahuan tentang prinsip, metode dan praktik tata kota di Nusantara yang dirumuskan pada dekade ketiga abad ini. Sosok di balik perencanaan Kebayoran Baru adalah dua tokoh penting: H. Mohammad Soesilo dan Thomas Karsten. Dua warisan konseptual Karsten yang diterapkan Soesilo dalam perencanaan Kebayoran Baru, yakni konsep 'campuran sosial' dan 'keseluruhan organik', juga relevan bagi Indonesia pasca kemerdekaan. Kata kunci. Kebayoran Baru, pendekatan perencanaan, H. Mohammad Soesilo, Thomas Karsten